2020
DOI: 10.1016/j.compositesb.2019.107699
|View full text |Cite
|
Sign up to set email alerts
|

Strength and toughness trade-off optimization of nacre-like ceramic composites

Abstract: Bio-inspired by abalone nacre, all ceramic brick-and-mortar composites with impressive mechanical properties have been recently manufactured. Albeit comprising only brittle constituents, extrinsic reinforcement mechanisms impart to these nacre-like ceramics high toughness and non-catastrophic crack propagation properties. While several models have been developed to understand the mechanical properties of natural and synthetic brick-and-mortar materials, they have always considered a ductile interface and focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Nacre-like composite microstructure may be optimized in order to promote such fracture mechanisms and thus enhance the apparent macroscopic toughness increase. Numerical simulations at the building block scale may help understand the influence of key microstructural features and provide guidelines for the microstructure optimization, for instance by means of periodic cell modeling [10,11,12,13,14]. Begley et al [10] developed a micromechanical model taking into account elastic perfectly plastic interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nacre-like composite microstructure may be optimized in order to promote such fracture mechanisms and thus enhance the apparent macroscopic toughness increase. Numerical simulations at the building block scale may help understand the influence of key microstructural features and provide guidelines for the microstructure optimization, for instance by means of periodic cell modeling [10,11,12,13,14]. Begley et al [10] developed a micromechanical model taking into account elastic perfectly plastic interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…A resulting design recommandation was, for instance, a high platelet volume fraction with platelets five time stronger than the interface. Discrete element modeling was recently used [13,14] to simulate fracture in brick-and-mortar structures. Abid et al [13] highlighted the importance to control the architecture in order to minimize statistical microstructure variations and concluded that interfaces with large fracture toughness to strength ratio are more likely to maximize energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the specific case of materials consisting of a matrix that cements aggregates not in direct contact, these constitutive relations establish interactions between the aggregates when they are within an interaction range greater than the distance between the centroids of the aggregates [18]. This allows the study of damage in homogeneous materials such as ceramics [20] and heterogeneous materials such as concrete [21][22][23], rock [24], or composites with a brick and mortar architecture (both natural [25,26] and man-made composites, such as brick masonry). The identification of adequate cohesion laws between particles in direct contact is of fundamental importance to obtain an accurate modeling of the continuity of matter [27].…”
Section: Introductionmentioning
confidence: 99%
“…In the specific case of materials consisting of a matrix that cements aggregates not in direct contact, these constitutive relations establish interactions between the aggregates when they are within an interaction range greater than the distance between the centroids of the aggregates [13]. This allows the study of damage in homogeneous materials such as ceramics [15] and heterogeneous materials such as concrete [16][17][18], rock [19], or composites with a brick and mortar architecture (both natural [20,21] and man-made composites, such as brick masonry). The identification of adequate cohesion laws between particles in direct contact is of fundamental importance to obtain an accurate modeling of the continuity of matter [22].…”
Section: Introductionmentioning
confidence: 99%